The Role Of Periapical Radiography As A Clinical Guide In The Bypass Procedure Of A Fractured Endodontic File In The Root Canal Of Tooth 22: A Case Report - Agung Nugroho; Nilasary Rochmanita Suparno; Cahyani Cahyani; Aulia Salsabila Agata (International Journal of Health Engineering and Technology, 2026)
Instrument fracture is one of the most common procedural complications encountered in endodontic treatment, with an incidence ranging from 0.25% to 10%. A fractured file retained within the root canal may hinder adequate debridement and obturation, thereby significantly affecting the prognosis of treatment. Periapical radiography plays a crucial role as both a diagnostic modality and a clinical guide in the management of such cases. This case report describes the management of a fractured instrument in the root canal of tooth 22 (maxillary left lateral incisor) using a radiographically guided bypass technique. A 36-year-old male patient presented for continuation of root canal treatment on tooth 22; however, during intracanal medicament placement following canal preparation, the lentulo file fractured. Periapical radiographic examination confirmed the presence of a fractured instrument along the root canal accompanied by a periapical radiolucent lesion. A bypass technique was performed under periapical radiographic guidance at every stage of the procedure, including working length determination, instrument position confirmation, and post-obturation evaluation. Post-treatment radiographic assessment demonstrated hermetic obturation with improvement of the periapical radiolucency at the three-month follow-up. This case report emphasizes that periapical radiography serves as the primary clinical guide in bypass procedures for fractured endodontic instruments within the root canal.